2023
DOI: 10.1101/2023.09.14.557555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aminergic and peptidergic modulation of Insulin-Producing Cells inDrosophila

Martina Held,
Rituja S. Bisen,
Meet Zandawala
et al.

Abstract: Insulin plays a critical role in maintaining metabolic homeostasis. Since metabolic demands change momentarily, insulin release needs to be constantly adjusted. These adjustments are mediated via distinct pathways, most prominently the blood glucose level, but also feedforward signals from motor circuits, and different neuromodulatory pathways. Here, we analyzed how neuromodulatory inputs control the activity of the main source of insulin in Drosophila — a population of Insulin-Producing Cells (IPCs) located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Hence, DH44Ns strongly and significantly inhibited IPCs. Notably, we also recorded from one IPC, which was excited during DH44N activation and inhibited immediately after cessation of activation (Supplementary Figure S4C), indicating heterogeneity in the IPC population 30 . Overall, our results indicate that acute activation of DH44Ns inhibits IPC activity, hence regulating insulin release.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Hence, DH44Ns strongly and significantly inhibited IPCs. Notably, we also recorded from one IPC, which was excited during DH44N activation and inhibited immediately after cessation of activation (Supplementary Figure S4C), indicating heterogeneity in the IPC population 30 . Overall, our results indicate that acute activation of DH44Ns inhibits IPC activity, hence regulating insulin release.…”
Section: Resultsmentioning
confidence: 92%
“…For example, the line labels a subset of DH44Ns ascending from the VNC. A pair of these DH44Ns co-express the neuropeptide Leucokinin (LK) 69 , and LK expressing neurons inhibit most IPCs 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our prediction, our analysis indicated that multiple receptors for clock peptides are indeed expressed in NSC. Modulatory inputs to m-NSC DILP have been examined extensively and our analysis is in agreement with previous expression and functional studies (Kapan et al ., 2012, Nässel and Vanden Broeck, 2016, Nagy et al ., 2019, Oh et al ., 2019, Held et al ., 2023). Taken together, our analysis uncovers the molecular substrates of paracrine signaling between clock neurons and NSC.…”
Section: Resultsmentioning
confidence: 99%